THE COMPONENT CHARACTERISTICS OF A FAVORITE TEACHER IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 (Study in verses 129 and 151 of Surah al-Baqarah) مكونات شخصية المعلم المختارة في عصر الثورة الصناعية الرابعة (دراسة من خلال آيتي 129 و 151 من سورة البقرة) - Moh. Abdul Kholiq Hasan (Universitas Muhammadiyah Surakarta, 2022)
This research aims to investigate the components of chosen teachers’ characteristics in the industrial revolution era 4.0 based on the cue of verse 129 and 151 of surah al-Baqarah. It employed library research method with descriptive qualitative approach. Content analysis theory was used to analyze the texts of verse 129 and 151 of surah al-Baqarah and related commentaries with the contextualization approach of the Qur'an. The results indicate that the components of chosen teachers’ characteristics in the industrial revolution era 4.0 fit with the cue of verse 129 and 151 of surah al-Baqarah as follows: (1) Having extensive reading and consistent with al-Quran and science and technology related to industry 4.0, (2) Teaching al-Quran and writing, including electronic writing, (3) Teaching wisdom in the form of expertise in interacting with the development of industrial technology 4.0, (4) Purifying the soul from all badness including paying attention to practical ethics with industrial technology 4.0, (5) Continue to increase knowledge of industrial technology 4.0.Penelitian ini bertujuan untuk mengetahui kompenen karakter guru pilihan di era revolusi indrustri 4.0 sesuai isyarat ayat 129 dan 151 surah al-Baqarah. Menggunakan metode penelitian perpustakaan dengan pendekatan deskreptif kualitatif. Teori konten analisis digunakan untuk menganalisis teks ayat 129 dan 151 surah al-Baqarah dan karya tafsir terkait dengan pendekatan kontentualisasi al-Qur`an. Hasil penelitian menunjukkan bahwa komponen karakter guru pilihan di era revolusi indrustri 4.0 sesuai isyarat ayat 129 dan 151 surah al-Baqarah adalah (1). Memiliki bacaan yang luas dan konsisten terhadap al-Quran dan ilmu teknologi terkait industri 4.0 (2). Mengajarkan al-Qur`an dan penulisan, termasuk penulisan elektronik (3). Mengajarkan hikmah berupa keahlian dalam berinteraksi dengan perkembangan teknologi indrustri 4.0 (4). Membersihkan jiwa dari segala keburukan termasuk memperhatikan etika praktik dengan teknologi indrutri 4.0. (5) Terus menambah pengetahuan teknologi industri 4.0.ملخص: تهدف الدراسة معرفة مكونات شخصية المعلم المختارة في عصر الثورة الصناعية 4.0 من خلال دراسة آيتي 129 و 151 من سورة البقرة. تعتمد هذه الدراسة منهج البحث المكتبي الوصفي التحليلي بتحليل آراء المفسرين واستنباطاتهم تجاه آيتي 129و 151 من سورة البقرة، بطريقة تحليل المحتوي أو ما يسمى بــ (content analysis)، مع إظهار فهم سياق الآيات للواقع والحياة الإنسانية. وقد أظهرت نتائج الدراسة، أن مكونات شخصية المعلم المختارة في عصر الثورة الصناعية 4.0 كما أشارت إليها آيتا 129و 151 من سورة البقرة، هي: (1) التلاوة الواسعة والمستمرة سواء كان المتلو هو القرآن أوغيره من العلوم التطبيقية و التقنية الحديثة. (2) تعليم الكتاب والكتابة، لتشمل معنى الكتابة، الكتابة الإلكترونية (3) تعليم الحكمة وهي الملكة في التعامل مع التقنية الرقمية التي هي من سمة عصر الثورة الصناعية 4.0 (4). تزكية النفوس و الاهتمام بالممارسة الاخلاقية (Ethical Practice) في التعامل مع التطور التكنولوجي في عصر الثورة الصناعية 4.0. (5) الاستزادة المستمرة من العلوم التقنية المبتكرة في عصر الثورة الصناعية الرابعة (4.0)